Effectiveness of global warming disaster mitigation e-module in increasing students' creative thinking - Habibah, Rahmi; Fauzi, Ahmad (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Global warming is an environmental problem that has a broad impact on human life and ecosystems. Disaster mitigation due to global warming is a crucial step that needs to be implemented in various aspects, including education. The Merdeka Curriculum emphasizes project-based learning and innovation, so that the development of e-modules based on disaster mitigation with a guided inquiry approach is a relevant solution for improving students' creative thinking skills. Methods: This research uses the Research and Development (R&D) method with the Van den Akker model in developing e-modules, as well as a quasi-experimental approach with a pretest-posttest control group design to test its effectiveness. The research subjects were class X students at MAN 3 Mandailing Natal who were selected using a purposive sampling technique. The research instrument is a creative thinking test which is validated by experts and tested for reliability. Data analysis was carried out using the N-Gain test and the Mann-Whitney test. Findings: The research results showed that the experimental class that used guided inquiry-based e-modules experienced a higher increase in creative thinking skills than the control class. The average N-Gain score for the experimental class was 0.66 (high category) while the control class was only 0.33 (low category). The Mann-Whitney test showed a significant difference between the two groups (Asymp. Sig. < 0.05), indicating the effectiveness of the e-module in improving creative thinking skills. Conclusion: This research confirms that e-modules based on disaster mitigation with a guided inquiry approach are effective in improving students' creative thinking skills. Novelty/Originality of this article: The novelty of this research lies in the integration of e-modules in disaster mitigation learning in the Merdeka Curriculum, which has not been studied much before. The authenticity of this research is supported by an experimental approach and measurement based on structured creative thinking indicators.